Contrasting the effectiveness and efficiency of virtual reality and real environments in the treatment of acrophobia - Coelho, Carlos M. (2008)
Previous studies reported good results in using virtual reality for the treatment of acrophobia. Similarly this paper reports the use of a virtual environment for the treatment of acrophobia. In the study, 10 subjects were exposed to three sessions of simulated heights in a virtual reality (VR) system, and 5 others were exposed to a real environment. Both groups revealed significant progress in a range of anxiety, avoidance and behaviour measurements when confronted with virtual as well as real height circumstances. Despite VR participants experiencing considerably shorter treatment times than the real-world subjects, significant improvements were recorded on the Behavioural Avoidance Test, the Attitudes Toward Heights Questionnaire and the Acrophobia Questionnaire. These results are suggestive of a possible higher effectiveness and efficiency of VR in treating acrophobia.